2022
DOI: 10.3390/biom12081066
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Binds to Transthyretin with Low Affinity

Abstract: The plasma protein transthyretin (TTR), a transporter for thyroid hormones and retinol in plasma and cerebrospinal fluid, is responsible for the second most common type of systemic (ATTR) amyloidosis either in its wild type form or as a result of destabilizing genetic mutations that increase its aggregation propensity. The association between free calcium ions (Ca2+) and TTR is still debated, although recent work seems to suggest that calcium induces structural destabilization of TTR and promotes its aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We also examined the stability of A97S‐TTR at physiological pH using S‐Trap experiments, in which SDS was used to impel the unfolding of stable proteins and calcium‐mediated destabilization (Cantarutti et al, 2022; Palmieri Lde et al, 2010; Wieczorek et al, 2021). With the increased incubation time at 85°C, we found that monomeric A97S‐ and WT‐TTR, respectively, became the predominant species after 120 and 300 s (Figure 4a–c), suggesting that WT‐TTR was much more heat‐resistant than A97S‐TTR in the presence of SDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the stability of A97S‐TTR at physiological pH using S‐Trap experiments, in which SDS was used to impel the unfolding of stable proteins and calcium‐mediated destabilization (Cantarutti et al, 2022; Palmieri Lde et al, 2010; Wieczorek et al, 2021). With the increased incubation time at 85°C, we found that monomeric A97S‐ and WT‐TTR, respectively, became the predominant species after 120 and 300 s (Figure 4a–c), suggesting that WT‐TTR was much more heat‐resistant than A97S‐TTR in the presence of SDS.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous reports have revealed that Ca 2+ could interact with TTR with a pretty weak affinity, but still lead to the changes of conformational flexibility on TTR variants. (Cantarutti et al, 2022;Palmieri Lde et al, 2010;Wieczorek et al, 2021) In the presence of increased Ca 2+ concentrations from 0 to 100 mM, we found that monomeric species of A97S-TTR were gradually raised up to 40% while that of WT were still kept at $5%-10% in a 16-h incubation (Figure 4d, e), suggesting that the Ca 2+ effect on A97S was substantially stronger than that on WT proteins.…”
Section: Conformational Stability Of Ttr A97s Variantmentioning
confidence: 91%
“…In an experiment with rats by George et al, 99m Tc-PYP scintigraphy was performed 1 h after the administration of aggregated TTR to the heart, and the decrease in deposition by the anti-aggregated TTR antibody could be evaluated [33]. Moreover, it has been reported that TTR binds to Ca 2+ under high calcium concentrations and aggregates in vitro [34,35]. These findings suggest that 99m Tc-labeled bone tracers may bind and accumulate to amyloid itself or to Ca 2+ bound to the amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, it has long been established that a part of calcium also binds to prealbumin with an affinity similar to albumin. 22 Since calcium binds to both albumin and the nutritional marker prealbumin and its levels change with nutritional status, an important relationship network is in question. Magnesium and phosphorus, like calcium, are essential for bone mineralisation and many cellular functions.…”
Section: Introductionmentioning
confidence: 99%